INTEGRATION OF FOUR SKILLS OF THE ENGLISH LANGUAGE - `To’xtayeva Gulbahor Abduraim qizi; Pardayeva Aziza Rahmatullayevna (International Engineering Journal For Research & Development, 2023)
The application of a personality-oriented approach in foreign language lessons is one of the main problems in modern education. Much attention should be paid to the creation of such an educational environment at the university, in which further socialization of the individual takes place and professionally oriented skills of each student are developed. Each student is a person with their own needs and desires. The teacher needs to take into account all aspects of a personality-oriented approach when developing and implementing a foreign language course.